Remarks on the Tightening of Liability for Certain Traffic Offences (Ius Novum, 2024)
The author discusses the nature and scope of changes introduced to the Code of Petty Offences and the Code of Procedure in Petty Offences Cases by the Act of 2 December 2021. The amendment represents a drastic intervention by the legislator in the current legal framework regarding offences against safety and order in transportation. It foresees significant modifications in the legal and criminal response to these offences, transformations in the characteristics of selected types of prohibited acts, and proposes entirely new types of prohibited acts. The analysis suggests that the guiding principle behind these changes is to increase the degree of punitiveness of petty offences law towards perpetrators of traffic violations. This legislative approach raises concerns about the instrumental use of petty offences law with respect to the perpetrators of these offences. The adopted direction of changes raises suspicions that the legislator has not thoroughly familiarised themselves with the matter covered by their intervention. In any case, it is not grounded in the current state of traffic criminality, or in the analysis of judicial practice. An increase in repressiveness has never directly translated into a reduction in traffic criminality. The latter is a much more complex problem, involving the necessity of multi-faceted references.